2016
DOI: 10.1007/s00221-016-4790-6
|View full text |Cite|
|
Sign up to set email alerts
|

Can augmented feedback facilitate learning a reactive balance task among older adults?

Abstract: While concurrent augmented visual feedback of the centre of pressure (COP) or centre of gravity (COG) can improve quiet standing balance control, it is not known if such feedback improves reactive balance control. Additionally, it is not known if feedback of the COP or COG is superior. This study aimed to determine if: 1) concurrent augmented feedback can improve reactive balance control; and 2) feedback of the COP or COG is more effective. Forty-eight healthy older adults (60-75 years old) were randomly alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
2
7
1
Order By: Relevance
“…augmented feedback does not enhance motor learning in a reactive balance task (Mansfield et al, 2017). However, this is contrary to Sullivan et al (2008) and Wulf et al (2010) who found higher task performance for children receiving augmented feedback more frequently.…”
Section: Discussioncontrasting
confidence: 70%
“…augmented feedback does not enhance motor learning in a reactive balance task (Mansfield et al, 2017). However, this is contrary to Sullivan et al (2008) and Wulf et al (2010) who found higher task performance for children receiving augmented feedback more frequently.…”
Section: Discussioncontrasting
confidence: 70%
“…The feedback provided by the visual stimuli was given to the subjects to maintain balance in both static and dynamic positions. The validity and reliability of this tool have been confirmed in previous studies (10).…”
Section: Methodssupporting
confidence: 74%
“…6 However, although the positive effect of visual feedback on posture is found in healthy adults, [7][8][9][10] some researchers proposed that visual feedback of postural tasks might lead to greater arousal, resulting in a higher cognitive (attentional) load of postural control. 11 Since the attentional resource is more limited in patients with PD than healthy adults, higher attentional load of posture may exceed the available resource capacity in PD, especially in dual-task conditions, in which both postural task and suprapostural task compete for the limited attentional resource. 12 Thus, consensus remains elusive regarding how posture is controlled when patients with PD are presented with visual feedback from their actual postural performance.…”
Section: Introductionmentioning
confidence: 99%